Analisis Implementasi Penanganan Pembiayaan Mudhorobah Bermasalah di KSPPS BMT Bina Ummat Sejahtera Cabang Mijen Kudus - Riyadi, Fuad; Lestari, Sri Puji (Universitas Islam Negeri Sunan Kudus, 2017)
Mudharabah is a special kind of partnership between two parties, where one partner providers the capital executed (shahibul mal) and the other supplying the labor and skill as agent or manager (mudharib), for investing in a pre-determined activity, which grants each party a share of the earnings as determined at the time of the investment. On this Implementation while the risk in financing mudharabah, especially on this the financing application, high relatively, among other side streaming, negligence and misconduct willful, concealment of profits by customers when customers are not honest. The amount of financing risk is shown in the ratio of non-performing finance. The high of non-performing finance indicates the large number of borrowers who can’t repay their finance in accordance with the initial agreement that has been agreed between the bank and the customer, so financing becomes problematic. Funding problems can be caused by the bank itself, the customers or external parties. KSPPS BMT Bina Ummat Sejahtera Mijen Kudus has been anticipating the event of a dispute banking, especially in the provision of financing problems. On this theory of completion financing problems, be done with several measures including the rescue action by intensive bill, rescheduling, re-requirements and realignment. Rescue actions made by bank on this condition that the customer is still considered to have good faith to settle the payment.